2019
DOI: 10.14214/df.275
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compound fluxes from northern forest soils

Abstract: Emissions of biogenic volatile organic compounds (BVOCs) cool down the global climate via their impacts on aerosol and cloud formation. Climate change will likely have a major impact on BVOC fluxes from the biosphere, including soils, due to temperature-driven plant biosynthesis of volatile organic compounds (VOCs), compound volatility and microbial activity. Soils are a poorly quantified source of VOCs, where the diversity of driving factors creates high spatial and temporal variability in soil VOC fluxes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 147 publications
(273 reference statements)
0
2
0
Order By: Relevance
“…Rinnan et al (2013) found similar compounds as in our study, for example, 1-octene, to be induced by mechanical disturbance of subarctic heath vegetation. Furthermore, an increase in microbial release of BVOCs caused by an increased input of labile C from damaged roots and microbial communities might also have taken place (Mäki, 2019). Future research is encouraged to take into consideration the disturbance from installation equipment when designing experiments.…”
Section: Installation Disturbancementioning
confidence: 99%
See 1 more Smart Citation
“…Rinnan et al (2013) found similar compounds as in our study, for example, 1-octene, to be induced by mechanical disturbance of subarctic heath vegetation. Furthermore, an increase in microbial release of BVOCs caused by an increased input of labile C from damaged roots and microbial communities might also have taken place (Mäki, 2019). Future research is encouraged to take into consideration the disturbance from installation equipment when designing experiments.…”
Section: Installation Disturbancementioning
confidence: 99%
“…Most research on sBVOCs has focused on emissions, measured either from excavated soil samples in laboratories (Bourtsoukidis et al, 2018; Kramshøj et al, 2018; Leff & Fierer, 2008) or from soil surfaces, with or without a litter layer, in the field (Asensio, Peñuelas, et al, 2008; Kramshøj et al, 2016). Only few studies have examined BVOC concentrations in the soil, and sampling methods are not well established yet (Albers et al, 2011; Mäki, 2019; Smolander et al, 2006). A major concern associated with sampling in the soil environment is that sampling procedures may cause disturbance that affects the measured concentrations (Van der Putten et al, 2001).…”
Section: Introductionmentioning
confidence: 99%